Kathakali - Balakrishnan, S.; Pasricha, Avinash (New Delhi : Wisdom Tree, 2004)
In this book, the actual practitioners of Kathakali dance forms, the dancers themselves, give the insider's point of view, the origin and history, the music, the costumes, make-up and specific jewellery
Keywords: Dance -- Kerala -- India; Dance -- Kerala -- India -- Origin; Dance -- Kerala -- India -- Equipments and supplies; Kathakali(Dance) -- Kerala -- India